2014
DOI: 10.1016/j.bjorl.2014.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Postural control in Parkinson's disease

Abstract: Postural imbalance in Parkinson's disease patients is characterized by the abnormalities of weight distribution index, synchronization index, Fourier transformation index, and fall index as measured by Tetrax™ posturography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
0
14
0
6
Order By: Relevance
“…Postural sway during quiet standing in PD is another parameter of postural control, which has been studied previously using different force platforms to measure COP displacement in various sensory conditions [3,5,6,9,10,24,25,[27][28][29]. The present study revealed that patients with PD had a greater COP area than healthy subjects under the following test conditions: open eyes; closed eyes; inaccurate somatosensory information and closed eyes; dynamic visual field; and visual-vestibular interaction.…”
Section: Near Here>mentioning
confidence: 74%
“…Postural sway during quiet standing in PD is another parameter of postural control, which has been studied previously using different force platforms to measure COP displacement in various sensory conditions [3,5,6,9,10,24,25,[27][28][29]. The present study revealed that patients with PD had a greater COP area than healthy subjects under the following test conditions: open eyes; closed eyes; inaccurate somatosensory information and closed eyes; dynamic visual field; and visual-vestibular interaction.…”
Section: Near Here>mentioning
confidence: 74%
“…This disease is one of the most important chronic diseases in elderly people. Among the main symptoms of Parkinson's disease is the tremor in the hands and feet at rest, slow movements, the stiffness of the arms and legs as well as the lack of postural balance (Fukunaga et al, ). The probability of development of this disease increases as the individual grows up and becomes older, and about 1.8% of people aged over 65 develop this disease (Aminoff et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Posturography is an objective research tool that allows the analysis of postural sway in both the sagittal and frontal planes [16]. Looking through the various studies, it may be noted that the assessment of balance with a balance platform is very popular, because it is a tool that is easy to use, gives quantitative results and explores the greatly precise activity of the balance of a human.…”
Section: Discussionmentioning
confidence: 99%